Women in medicine - navigating a complex world - Tiwari, Sucheta (Research and Humanities in Medical Education, 2020)
Widely publicised allegations of sexual abuse have thrown light on the issue of gender-based discrimination women face in many industries. Workplaces are now being redesigned to suit women's needs. Medicine has a bidirectional relation with society. It is shaped by society, and its ideas often shape society in return. This article attempts to explore the relationship medicine has with women. It assesses how traditional gender roles were defined by medicine as desirable ideals of health. It looks at historical gender-based biases inherent in the study and practice of medicine. It attempts to view women's health beyond their reproductive function. And lastly, it explores gender biases within medicine as a profession, in the hope of initiating a conversation and bringing about positive change in the field. The author acknowledges that gender has been treated as binary in this article, and admits that the decision was made to simplify the narrative.